2017
DOI: 10.1186/s12891-017-1423-6
|View full text |Cite
|
Sign up to set email alerts
|

The association of lumbar curve magnitude and spinal range of motion in adolescent idiopathic scoliosis: a cross-sectional study

Abstract: BackgroundSpinal deformities affect the overall alignment of the spine and thus the vectors of loading on the lumbar region and intervertebral discs. Due to wedging of the disc or vertebrae of unbalanced spinal segments, alignment change may affect the range of motion (ROM) of individual spinal segments or the global spine. This is particularly important in adolescent idiopathic scoliosis (AIS) patients who may suffer from early degeneration, back stiffness and pain. Hence, this study aimed to determine the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
2
26
0
2
Order By: Relevance
“…Hence, the results of this study do not indicate the duration of brace wear required. In addition, curve flexibility has been shown to greatly influence the outcomes of bracing and surgery [ 32 33 34 35 ]. This aspect of bracing, as well as the varied responses of different curve patterns, is beyond the intent of this study and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the results of this study do not indicate the duration of brace wear required. In addition, curve flexibility has been shown to greatly influence the outcomes of bracing and surgery [ 32 33 34 35 ]. This aspect of bracing, as well as the varied responses of different curve patterns, is beyond the intent of this study and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…As AIS is a three-dimensional deformity, management should not be focused only on the coronal plane. The coronal and sagittal plane deformities are coupled and thus, variations in the coronal plane may translate into sagittal plane changes [ 3 5 ]. Mac-Thiong et al [ 6 ] evaluated the sagittal alignment of 160 patients with AIS and found less thoracic kyphosis in thoracic major curves compared to lumbar curves, and lumbar curve patients tend to have larger lumbar lordosis.…”
Section: Introductionmentioning
confidence: 99%
“…Scoliosis is not necessarily a deadly disease, but it affects the patients’ cosmesis, mobility, pain and quality of life [ 21 , 22 ]. The diagnosis and management decision of scoliosis relies on the Cobb angle measurement and thus these measurements must be accurate and consistent.…”
Section: Discussionmentioning
confidence: 99%